MITIGASI BENCANA BERBASIS MANGROVE DI DESA APAR, PARIAMAN UTARA, SUMATERA BARAT: ANALISIS PERSEPSI MASYARAKAT DAN PEMODELAN ISM - Ithvi Marhamah; Rama Nanda; Siti Aisyah; Fadli Pradana (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2026)
Apar Village, North Pariaman District, West Sumatra, is a coastal area vulnerable to shoreline erosion caused by Indian Ocean dynamics and anthropogenic pressures. This study aims to analyze community perceptions of mangrove ecosystem functions as a coastal disaster mitigation system and to identify key factors influencing mangrove management using Interpretive Structural Modeling (ISM). Data were collected through in-depth interviews, questionnaires distributed to 50 respondents using a Likert scale, and field observations. The results show that local communities have a relatively good understanding of mangrove ecological functions in reducing coastal abrasion and protecting coastal areas. MICMAC-ISM analysis indicates that the role of village government (A2), village regulations (A7), and NGO involvement (A3) are independent factors with the highest driver power in the system. Community awareness, participation, economic benefits, and local institutional capacity are categorized as linkage factors, while environmental education and mangrove destruction threats are dependent factors. The findings suggest that strengthening village institutions, local regulations, and community participation are essential strategies for sustainable mangrove-based disaster mitigation in Apar Village.